Rural Urban Disparity in and around Surabaya Region, Indonesia - Vely Kukinul Siswanto; Jayant K. Routray; Rima Dewi (IPTEK The Journal for Technology and Science, 2014)
A shift in development towards the outskirts of urban areas changes the characteristics of the region and can ultimately lead to urban disparities in economic and social terms. The current study has tried to divide the study area covers the areas of surrounding Surabaya as urban, peri urban and rural areas with reference to three time periods (2008, 2009 and 2010) and shows that the typology in the study area changes each year. Furthermore, based on the theil index analysis, using a number of pre-prosperous household for social disparity and per capita GDP (Gross Domestic Product) for economic disparity shows that urban and peri urban areas have medium and high level of social and economic disparity compare with rural area which have low levels of disparity. Through multivariate correlation analysis can be seen that the health center distance, electricity and water users effecting the social disparity. Moreover, the financial, industrial, electricity, trade, construction, transportation, agriculture, and mining sector's productivity have a significant relationship with the economic disparity. Health facilities, water and electricity improvement strategies to be followed for reducing the social disparity. Electricity improvement, water, services sector, transportation infrastructure, and industrial development to reduce the economic disparity.